2021
DOI: 10.51594/ijmer.v2i7.185
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Issue of Business Fraud in Burkina Faso: What Best Prevention Device?

Abstract: This study shows the state of fraud in businesses in Burkina Faso while diagnosing anti-fraud schemes. Thanks to this research carried out on Burkinabè companies, the results show that fraud affects all sectors of activity. It also exposes the limits of anti-fraud systems, which are essentially: the limits of the organizational framework, the weakness of the internal control system and the lack of an anti-fraud culture. To conduct our research, a quantitative approach is used to collect and interpret the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Overall UDS' internal auditing reveals a high degree of prevention. For Nacoulma, Akouwerabou and Nassè (2020) companies should understand that they are not invulnerable to fraud, and they should assess the risk of fraud and significantly reduce this risk. The current research recommends the following based on its findings: 1.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Overall UDS' internal auditing reveals a high degree of prevention. For Nacoulma, Akouwerabou and Nassè (2020) companies should understand that they are not invulnerable to fraud, and they should assess the risk of fraud and significantly reduce this risk. The current research recommends the following based on its findings: 1.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…On the other hand, Efficiency becomes the first key success factor for companies over 51 million XOF and adaptation to Africa becomes the least valuated key success factor for companies over 3 billion XOF DISCUSSION Previous research in the same context have shown that the eradication of corruption is the the key success factors for African companies (Bako & Akouwerabou, 2014). For some other authors the eradication of insane business practices and the eradication of fraud are some key factors for success (Nacoulma, Akouwerabou, & Nassè, 2020;Nassè, 2016). According to some authors it is rather the management methods that should undergo through a hybridization process for companies to get a full success (Illa, 2012;Shamba & Livian, 2014;.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…Some studies show the lack of consistent business ethical practices in both public and private institutions in the West African context, and how these practices affect its economy and its development (Nacoulma, Akouwerabou & Nassè, 2020;Nassè, 2020;Akouwerabou & Bako, 2014). The present research is conducted in some private companies because in the context there are some challenges and major obstacles to conduct research in public companies.…”
Section: Introductionmentioning
confidence: 99%